UQCRC1 variants in early-onset and familial Parkinson's disease in a Taiwanese cohort - Liao, Ting-Wei; Chao, Chih-Ying; Wu, Yih-Ru (Frontiers in Neurology, 2022)
(1) Background: A recent Taiwanese study reported variants of the ubiquinol-cytochrome c reductase core protein 1 (UQCRC1) gene linked to autosomal dominant parkinsonism with polyneuropathy. This study investigated the pathogenicity of UQCRC1 in a Taiwanese cohort of patients with Parkinson’s disease (PD). (2) Method: This study involved 107 participants (98 with early-onset PD and 9 with familial PD). All UQCRC1 coding exons and exon–intron boundaries were sequenced. The rarity and pathogenicity of the identified variants were analyzed. The carrier frequencies of our cohort and the Taiwan Biobank were compared through a Pearson's χ2 or Fisher’s exact test along with Bonferroni corrections. (3) Results: Three missense variants (c.643G>C, p.D215H; c.800C>G, p.P267R; and c.923A>G, p.N308S) and seven rare variants were identified. No significant differences in the missense-variant carrier frequency were noted between our cohort and individuals in the Taiwan Biobank. Furthermore, no significant associations were noted between the variants and the risk of PD. (4) Conclusions: Our study is not supporting a role of UQCRC1 variants in PD.